2021
DOI: 10.3390/ijerph18020611
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Sensitivity and Compassion Satisfaction as Risk/Protective Factors from Burnout and Compassion Fatigue in Healthcare and Education Professionals

Abstract: The study analyzes sensory processing sensitivity and the compassion satisfaction as risk/protective factors against burnout and compassion fatigue, during the first period of the COVID-19 health emergency. A sample of 1566 Spanish adult healthcare (n = 694) and education (n = 872) professionals was evaluated. An ad hoc questionnaire for sociodemographic data, and the highly sensitive person scale (HSPS), Maslach burnout inventory (MBI) and professional quality of life scale (ProQOL-vIV) were administered. Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 34 publications
4
33
0
6
Order By: Relevance
“…Whereas previous research was often done in clinical (child) populations of patients with neurodevelopmental symptomatology, with known medical conditions that influence sensory processing as well as coping with stress, our study shows that sensory processing is also related to perceived stress in healthy workers. Our results add to recent studies that focused on the association of sensory processing sensitivity and occupational burnout [ 20 , 21 ]. Risk of burnout is not only heightened by the more static vulnerability of personality traits such as ‘hypersensitive persons’, but is probably also increased in individuals with neurodevelopmental difficulties in sensory processing.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Whereas previous research was often done in clinical (child) populations of patients with neurodevelopmental symptomatology, with known medical conditions that influence sensory processing as well as coping with stress, our study shows that sensory processing is also related to perceived stress in healthy workers. Our results add to recent studies that focused on the association of sensory processing sensitivity and occupational burnout [ 20 , 21 ]. Risk of burnout is not only heightened by the more static vulnerability of personality traits such as ‘hypersensitive persons’, but is probably also increased in individuals with neurodevelopmental difficulties in sensory processing.…”
Section: Discussionsupporting
confidence: 77%
“…Whether sensory processing difficulties may serve as precursors or markers for occupational burnout, is largely unknown. Some studies described an association of sensory processing sensitivity with burnout [ 20 , 21 ]. However, these studies measured the concept of ‘sensory processing sensitivity’, which represents a proposed personality trait characterized by deeper cognitive processing of stimuli and heightened emotional reactivity, and is conceptually different from (or even unrelated to) the more neurological approach of sense-based processing and related sensory processing disorders (SPD) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This gratification that accompanies helping others, either interpersonally or professionally, has been shown to protect against psychological distress in helping vocations. CS can also counteract the development of burnout and distress (Pérez-Chacón et al, 2021); likewise, our participants with higher CS reported lower levels of burnout. Few studies have measured the rates of CS in HCWs during the pandemic.…”
Section: Discussionsupporting
confidence: 58%
“…Empathy levels in practitioners and therapists are quite variable. Health care professionals with high levels of empathy seem to be more vulnerable to stress-related mental conditions ( e.g ., burn out/exhaustion and compassion fatigue)[ 65 - 67 ] with a protective role of compassion satisfaction, and sensory processing sensitivity as a risk factor[ 68 ].…”
Section: Discussionmentioning
confidence: 99%